1686 Review of Cyclical Vomiting Syndrome in a General Paediatric Hospital over a 12 Year Period. (October 2012) - Odumusi, K; Mahony, MJ; Atif, K; Jamal, B; Obi, C; Murphy, AM
Abstract : Background and Aims: Cyclical vomiting syndrome (CVS) is a chronic disorder characterised by recurrent episodes of vomiting separated by symptom free periods. Aim is to review the epidemiology, history, investigation and treatment of children diagnosed with CVS in Mid Western Regional Hospital Limerick from January 2000 to December 2011. Methods: This is a retrospective study of the cases that met the criteria for the diagnosis of CVS. Cases were identified using the hospital in-patient enquiry scheme (HIPE) data. Each patient's case file was assessed for the review. Results: A total of 89 cases of recurrent vomiting were identified using the HIPE data. 10 cases of CVS were identified. Age of onset ranged from 5 to 13 years. 8(80%) of patients were female. There was an average of 18 months between the onset of symptoms and establishment of diagnosis. Average duration of vomiting episodes was 5 days and average frequency was 6 weekly. 1(10%) had a positive family history of CVS while 4(40%) had a family history of migraine. 3(30%) had associated migraine. 9(90%) of patients had abdominal x-ray and upper GI contrast study while 5(50%) had upper GI endoscopy and abdominal ultrasound scan. 3(30%) had brain MRI and 1(10%) had laparoscopy and MRCP. 9(90%) of patients were treated with ondasetron, 8(80%) with proton pump inhibitors and 3(30%) with cyclizine during episodes. 2(20%) required psychiatric input. Conclusions: CVS is a disabling condition with female predominance. There is often a delay in diagnosis and large expenditure on investigations before diagnosis is made.